Thermosynergistes pyruvativorans gen. nov., sp. nov., an anaerobic, pyruvate-degrading bacterium from Shengli oilfield, and proposal of Thermosynergistaceae fam. nov. in the phylum Synergistetes. Issue 9 (28th September 2021) - Yang, Min; Li, Jiang; Lv, Xiao-meng; Dai, Li-rong; Wu, Ke-jia; Tu, Bo; Lawson, Paul A.; Tang, Yue-qin; Cheng, Lei
Abstract : A strictly anaerobic, thermophilic, Gram-stain-negative bacterium, named as strain S15 T, was isolated from oily sludge of Shengli oilfield in PR China. Cells of strain S15 T were straight or slightly curved rods with 0.4–0.8 µm width × 1.4–3 µm length and occurred mostly in pairs or short chains. Endospore-formation was not observed. The strain grew optimally at 55 °C (range from 30–65 °C), pH 6.5 (pH 6.0–8.5) and 0–30 g l −1 NaCl (optimum with 10 g l −1 NaCl). Yeast extract was an essential growth factor for strain S15 T . The major cellular fatty acid was iso-C15 : 0 (58.2 %), and the main polar lipids were amino phospholipid (APL), glycolipids (GLs) and phosphatidylethanolamine (PE). The G+C content of DNA of strain S15 T was 52.2 mol%. Strain S15 T shared 89.8 % 16S rRNA gene similarity with the most related organism Acetomicrobium hydrogeniformans DSM 22491 T in the phylum Synergistetes . The paired genomic average amino acid identity (AAI) and percentage of conserved proteins (POCP) values showed relatedness of less than 58.0 and 39.7 % with type strains of the species in the phylum Synergistetes . On the basis of phenotypic, phylogenetic and phylogenomic evidences, strain S15 T constitutes a novel species in a novel genus, for the name Thermosynergistes pyruvativorans gen. nov., sp. nov. is proposed. The type strain is S15 T (=CCAM 583 T =JCM 33159 T ). Thermosynergistaceae fam. nov. is also proposed.